HIV care among patients with presumptive tuberculosis in Masvingo district of Zimbabwe, 2017: how well are we doing? - Chamunorwa Ndudzo; Jaya Prasad Tripathy; Fortune Tauro; Clemence Sibanda; Maikoro Chiramba; Amadeus Shamu; Kudzai Masinire; Tafadzwa Muchengwa; Ajay MV Kumar (The Pan African Medical Journal, 2019)

(untitled)
INTRODUCTION: While HIV care among tuberculosis (TB) patients is successfully implemented and monitored, it is not routinely reported among "presumptive TB patients without TB". The present study describes the ascertainment of HIV status and receipt of antiretroviral therapy (ART) and the associated factors among presumptive TB patients (with and without TB) in 35 public health facilities of Masvingo district of Zimbabwe from January to June 2017. METHODS: this was an analysis of secondary programme data. We performed log binomial regression to calculate adjusted relative risks (aRR) and 95% confidence intervals (CI). RESULTS: of 1369 presumptive TB patients, 1181 (86%) were ascertained for HIV status (98% among those subsequently diagnosed with TB, 83% among non-TB). Of them, 748 (63%) were HIV positive, more among TB patients (69%) than those without TB (61%). Among HIV-positive patients, 475 (64%) received ART, significantly higher among TB patients (78%) compared to those without TB (57%). Patients without TB were significantly more likely to have non-ascertained for HIV status (aRR=2.4, 95% CI=1.4-5.0) and not receiving ART (aRR=1.8, 95% CI=1.6-2.0), compared to those with TB. CONCLUSION: we found high rates of HIV status ascertainment among presumptive TB patients. But, ART uptake was poor among "presumptive TB patients without TB" despite implementation of "test and treat" strategy in Zimbabwe. The programme should step up the monitoring of HIV status and ART receipt among presumptive TB patients, by introducing an indicator in the quarterly reports of the national TB programme.